2011
DOI: 10.1097/fbp.0b013e328345ca1c
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine-induced impulsive action

Abstract: A conjunctive variable-interval differential-reinforcement-of-low-rate (VI-DRL, n= 18) responding schedule and a stop-signal task (n= 18) were used to evaluate the disinhibiting effects of nicotine on response withholding in rats. Sucrose solution was used to reinforce responding, and after a stable baseline was achieved under saline-administration conditions, 0.3 mg/kg nicotine was delivered before each session. Experiment 1 showed that repeated, but not the initial, administration of nicotine decreased perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 46 publications
3
10
1
Order By: Relevance
“…This result suggests that acute nicotine reduces response inhibition capacity in both strains. Although this finding is inconsistent with our expectations, it is consistent with nicotine-induced reductions in IRTs observed in DRL studies using Sprague Dawley rats (Kirshenbaum et al 2008, 2009, 2011). Performance in DRL schedules cannot be readily interpreted in terms of response inhibition capacity, because it is also sensitive to reinforcer-efficacy manipulations (e.g., reinforcer magnitude; Doughty and Richards 2002).…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…This result suggests that acute nicotine reduces response inhibition capacity in both strains. Although this finding is inconsistent with our expectations, it is consistent with nicotine-induced reductions in IRTs observed in DRL studies using Sprague Dawley rats (Kirshenbaum et al 2008, 2009, 2011). Performance in DRL schedules cannot be readily interpreted in terms of response inhibition capacity, because it is also sensitive to reinforcer-efficacy manipulations (e.g., reinforcer magnitude; Doughty and Richards 2002).…”
Section: Discussioncontrasting
confidence: 83%
“…Unlike humans, acute nicotine administration in rodents consistently decreases response inhibition capacity in a wide range of tasks, including the 5-CSRTT (Bizarro et al 2004; Blondel et al 2000; Hahn et al 2002; Semenova et al 2007), the differential reinforcement of low rates (DRL) schedule of reinforcement (Kirshenbaum et al 2011; Kirshenbaum et al 2009; Kirshenbaum et al 2008; Popke et al 2000a; Popke et al 2000b), the stop-signal task (Kirshenbaum et al 2011), and the go/no-go discrimination (Kolokotroni et al 2011). Only the temporal response differentiation task, which involves holding down a lever for a target interval, appears to be insensitive to nicotine-induced premature responding (Popke et al 2000b).…”
Section: Introductionmentioning
confidence: 99%
“…The observed effect of nicotine on the response-threshold is also consistent with the effects of nicotine on the performance of rats in other timing tasks that involve response withholding, such as the lever-holding task (Popke, Mayorga, Fogle, & Paule, 2000), the fixed-minimum interval schedule of reinforcement (Mazur et al, 2014), and the differential reinforcement of low rates schedule (Kirshenbaum, Jackson, Brown, Fuchs, Miltner, Doughty, 2011; Kirshenbaum, Johnson, Schwarz, & Jackson, 2009; Kirshenbaum, Brown, Hughes, Doughty, 2008; Popke et al, 2000). In these tasks, animals must withhold a response for a fixed interval to obtain reinforcement, and typically produce withholding intervals that are close to the withholding requirement.…”
Section: Discussionsupporting
confidence: 76%
“…Nicotine has been shown to produce disinhibitory behavior in the rats after subchronic peripheral nicotinic acetylchline receptor blockage (Ericson et al, 2000). It has also been suggested that response disinhibition in the variable-interval differential reinforcement of low rate responding and stop signal tasks are related in a systematic manner to nicotinic-acetylcholine receptor activation (Kirshenbaum et al, 2011). Thus it is possible that the loss of cholinergic tone produced by adolescent alcohol exposure seen in the present study could result in a “sensitization” of nicotinic receptors that promote the expression of disinhibitory behaviors under the conditions of stress/ food restriction such as those that occur in the modified open field conflict test.…”
Section: 0 Discussionmentioning
confidence: 99%